The epidemiological analysis of maxillofacial fractures in Italy: The experience of a single tertiary center with 1720 patients. Issue 8 (August 2017) - Bonavolontà, Paola; Dell'aversana Orabona, Giovanni; Abbate, Vincenzo; Vaira, Luigi Angelo; Lo Faro, Carmelo; Petrocelli, Marzia; Attanasi, Federica; De Riu, Giacomo; Iaconetta, Giorgio; Califano, Luigi
Abstract: Purpose: Maxillofacial fractures represent a serious public health problem. Their epidemiology is extremely variable, and its analysis is crucial to establish effective treatment and prevention of these injuries. However only two works have been published about maxillofacial fracture epidemiology in Italy. Materials and methods: The records of 1720 patients diagnosed with maxillofacial fractures in a 15-years period (2001–2015) in our department were retrospectively reviewed. Results: A total of 1108 male and 612 female patients were included in the study. The most frequent aetiology of fracture was road traffic injuries (57.1%), followed by assault (21.7%), falls (14.2%), work accidents (3.5%), sport accidents (3.3%) and other causes (0.2%). Significant variations of aetiology were detected between males and females and between Italians and individuals from other countries. The most frequently observed fracture involved the mandible (861 cases, 36%), followed by zygoma (489 cases, 20.4%), orbital walls (386 cases, 16.1%) and maxilla (282 cases, 11.8%). Conclusion: Road traffic legislation enforcement and continuous public education regarding the use of security devices remain an ongoing problem in our region and should be encouraged. In the same way, as migration flows influence and change the epidemiology of facial traumas, it is crucial to establish social support programs that avoid these disadvantaged categories of victims of violence and crime.